Mother–infant separations in prison. A systematic attachment-focused policy review. Issue 2 (4th March 2017) - Powell, Claire; Marzano, Lisa; Ciclitira, Karen
Abstract: Mothers in prison separated from their young children are an overlooked group. Attachment theory could provide a useful model to underpin interventions and better support women affected by separation from their infants. Current policy draws on a limited body of evidence and research has developed considerably since its first design. This review systematically searched all relevant UK prison policy and government documents with regards to mother and child separation in prison and analysed the extent to which these documents draw on attachment theory. Following initial searches, 58 documents were thematically analysed. Attachment was implicitly referred to in most documents but only explicitly mentioned in four. Global themes identified included 'separation as trauma'. However, document groups varied in focusing either on the mother or the child and there were no joint perspectives. Developing and researching specific attachment-informed interventions might be one way forward as would further attachment-based research in this area.